1992
DOI: 10.1001/archderm.1992.04530010083014
|View full text |Cite
|
Sign up to set email alerts
|

Scars on the Legs

Abstract: A 52-year-old black man was admitted to the county medical center for drug detoxification. He abused many drugs during the 30 years before admission, including intravenous heroin and cocaine. He also admitted to "skin popping" cocaine during the 3 years before admission. A dermatology consultation was requested for evaluation of multiple lesions of the legs of 2 years' duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…AzA long‐treatment for rosacea is safe and results in an improvement in skin texture , suggesting its possible interference with UV‐induced ECM integrity alteration. Although the mechanism of action of AzA is not completely understood, its anti‐inflammatory and ROS‐scavenging properties can be involved in the beneficial effects observed in the treatment for rosacea. We recently reported AzA as a modulator of inflammatory response in normal human keratinocytes by activating the peroxisome proliferator‐activated receptor γ (PPARγ) and inhibiting the trans‐activation of nuclear factor‐kB (NF‐kB) and the production of pro‐inflammatory cytokines and ROS .…”
Section: Introductionmentioning
confidence: 99%
“…AzA long‐treatment for rosacea is safe and results in an improvement in skin texture , suggesting its possible interference with UV‐induced ECM integrity alteration. Although the mechanism of action of AzA is not completely understood, its anti‐inflammatory and ROS‐scavenging properties can be involved in the beneficial effects observed in the treatment for rosacea. We recently reported AzA as a modulator of inflammatory response in normal human keratinocytes by activating the peroxisome proliferator‐activated receptor γ (PPARγ) and inhibiting the trans‐activation of nuclear factor‐kB (NF‐kB) and the production of pro‐inflammatory cytokines and ROS .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these compounds reveal a strong binding affinity to both proteins and their LBE scores are lower than the LBE score of vitamin D, which is considered a potential inhibitor [ 34 ]. Amazingly, our pharmacokinetic prediction results have shown that rutin, quercetin, catechin gallate, stigmasterol and campesterol have excellent analysis (LBE and K i ), which are better than the LBE and K i of the standard HIV-inhibitors (lopinavir and indinavir).The approved antiparasitic drugs by Food and Drug Administration (FDA), such as, ivermectin, spiramycin and praziquantel show good LBE scores and K i values for Nsp15 and weak interaction with 3CL pro as compared with other phytoconstituents compounds, which are not approved by the FDA for the treatment of any viral infection [ 35 , 36 ]. The docked structures of rutin, quercetin, catechin gallate, rhamnetin, stigmasterol, and control complexes of HIV-inhibitors (lopinavir and indinavir) with main protease 3CL pro and endoribonuclease of SARS-CoV-2 are presented in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…She was a cocaine sniffer; cocaine has been associated with multiple dermatological conditions such as itching, necrosis of the nasal septum after in halation, fibrosis after subcutaneous admin istration [4], systemic effects with vasculitis [5] and sclerodermiform characteristics of ANA on the hands associated with anticen tromere antibodies |6|; similarly, cutaneous thromboses have been associated with high intravenous dosages of cocaine [7|. More over.…”
Section: Discussionmentioning
confidence: 99%